Surplus Produsen Dan Surplus Konsumen Sayuran Lokal Di Pasar Teratai Bengkayang - Sabinus Beni; Manggu, Blasius (Cendekia Niaga, 2022)
The research was conducted at the Bengkayang Lotus Market, West Kalimantan to find out about producer and consumer surpluses as an effort to explore and analyze the problems that occur and can be used as a reference by the local government in making a policy related to market development in Bengkayang City, especially local traders who sell local vegetables. The research was conducted using qualitative methods with data collection techniques through in-depth interviews with local vegetable traders and buyers at the Bengkayang Lotus market to analyze producer surplus and consumer surplus of local vegetables. The results showed that firstly, consumers/buyers of local vegetables tend to enjoy and or receive profits (surplus) than traders (producers), secondly, several factors that influence the decrease and increase in demand and supply include: price, quality of vegetables (organic), service, as well as habits and third, the method of selling from house to house or traded directly in the market as factors that cause a surplus received by consumers and an increasing number of local vegetables are sold. The results of the study are expected to be a reference for the local government of Bengkayang Regency, West Kalimantan Province in making a policy that favors the community related to the development of the lotus market so that it can become an icon and at the same time a place to shop for basic needs that is comfortable and clean and at an affordable price, given the conditions Bengkayang which is directly adjacent to the Malaysian state of Sarawak so that the local wisdom in the Lotus Market can have a direct impact on traders and consumers.